Human MicroRNAs Interacting With SARS-CoV-2 RNA Sequences: Computational Analysis and Experimental Target Validation - Siniscalchi, Chiara; Di Palo, Armando; Russo, Aniello; Potenza, Nicoletta (Frontiers in Genetics, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel RNA virus affecting humans causing a form of acute pulmonary respiratory disorder named COVID-19, declared a pandemic by World Health Organization. MicroRNAs play an emerging and important role in the interplay between viruses and host cells. Although the impact of host microRNAs on SARS-CoV-2 infection has been predicted, experimental data are still missing. This study started by a bioinformatics prediction of cellular microRNAs potentially targeting viral RNAs; then, a number of criteria also based on experimental evidence and virus biology were applied, giving rise to 8 promising binding microRNAs. Their interaction with viral sequences were experimentally validated by transfecting luciferase-based reporter plasmids carrying viral target sequences or their inverted sequences into the lung A549 cell line. Transfection of reporter plasmids resulted in a reduction of luciferase activity for 5 out of the 8 potential binding sites, suggesting responsiveness to endogenously expressed microRNAs. Co-transfection of reporter plasmids along with microRNA mimics led to a further and strong reduction of luciferase activity, validating the interaction between miR-219a-2-3p, miR-30c-5p, miR-378d, miR-29a-3p, miR-15b-5p and viral sequences. miR-15b was also able to repress plasmid-driven Spike expression. Intriguingly, the viral target sequences are fully conserved in more recent variants such as UK variant B.1.1.7 and South Africa 501Y.V2. Overall, this study provides a first experimental evidence of the interaction between specific cellular microRNAs and SARS-CoV-2 sequences, thus contributing to understand the molecular mechanisms underlying virus infection and pathogenesis to envisage innovative therapeutic interventions and diagnostic tools.